การเตรียมและการใช้กากตะกอนเคลือบด้วยเหล็กออกไซด์สำหรับกำจัดโลหะจากน้ำ - ฐาปนพงศ์ พึ่งประสพ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
An absorbent for heavy metal ions was prepared using sewage sludge modified with iron-oxide. The modified adsorption method was used. The effect of sludge pretreatment temperature, pH of ferric solution and coating time were investigated. The adsorbents were prepared by using sludge pretreated at 300 degrees Celsius for 3 h coated with ferric solutions of pH 12. The coating time used was 1 h. The coated sludges were in amorphous form. Surface area, pore volume and iron content of the coated sludge were found to be higher than those of uncoated sludge. The optimum conditions for removal of heavy metal ions (Cu[superscript 2+], Cd[superscript 2+], Ni[superscript 2+] and Pb[superscript 2+]) from synthetic wastewater were studied using batch method. The concentrations of metal were determined by flame atomic absorption spectrometer (FAAS). The results showed that the pH suitable for adsorption of Cd[superscript 2+] and Ni[superscript 2+] was pH 7, Cu[superscript 2+] and Pb[superscript 2+] was pH 6 and pH 5, respectively. The contact time of 1 h. was used in adsorption experiments. The presence of NaNO[subscript 3], Ca(NO[subscript 3]) [subscript 2] and Na[subscript 2]SO[subscript 4] in metal solution in the level of 0.01 M and 0.50 M could reduce the adsorption capacity of the iron oxide coated sludge. The adsorption isotherm of Cu[superscript 2+], Cd[superscript 2+], Ni[superscript 2+] and Pb[superscript 2+] were defined by the function of Langmuir. The maximum adsorption capacity for Cu[superscript 2+], Cd[superscript 2+], Ni[superscript 2+] and Pb[superscript 2+] were 17.3, 14.7, 7.8 and 42.4 mg/g adsorbent, respectively. The removal efficiency of a mixed solution of Cu[superscript 2+], Cd[superscript 2+], Ni[superscript 2+] and Pb[superscript 2+] from real wastewater having initial concentration 19.9, 19.7, 19.5 and 51.5 mg/L, respectively using adsorbent dose of 10 g/L, was 99.9, 96.7, 82.2 และ 100.0 %, respectively. The iron oxide coated sludge showed a potential as adsorbent for water treatment.